Perception of the State Civil Apparatus in the Face of the Prabowo-Gibran Government's Expenditure Efficiency Policy at the Ministry of Home Affairs and the Regions - Maisono Saleh, Baiklah (International Journal of Law Social Sciences and Management, 2025)
This study aims to analyze the perception of functional State Civil Apparatus including Widyaiswara, Administrators, and Supervisor of the Implementation of Regional Government Affairs on the spending efficiency policies launched by the Prabowo-Gibran administration within the Ministry of Home Affairs and local governments. Expenditure efficiency policies are seen as an effort to create fiscal governance that is effective, effective, and by economic principles and state administrative laws. The study used a descriptive quantitative approach with a sample of 18 respondents for Widyaiswara, 60 respondents for Administrators, and 28 respondents for Supervisors of the Implementation of Local Government Affairs who were selected purposively. Data were collected through a closed-ended questionnaire and analyzed using descriptive statistics. The results of the study show that most State Civil Apparatus have a positive perception of the direction of spending efficiency policies, especially in the aspects of allocation efficiency and operational expenditure control. However, concerns were also found regarding the impact of the policy on the capacity to implement work programs and employee welfare. These findings recommend the need for a more intensive policy communication strategy and the involvement of functional State Civil Apparatus in formulating and evaluating the implementation of expenditure efficiency